"Besouro verde", novo depredador da laranjeira - Mariconi, Francisco A. M. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1962)
This paper deals with Iphimeis dives (Germar, 1824), a new Citrus noxious insect.